1984
DOI: 10.1172/jci111437
|View full text |Cite
|
Sign up to set email alerts
|

Role of circulating somatostatin in regulation of gastric acid secretion, gastrin release, and islet cell function. Studies in healthy subjects and duodenal ulcer patients.

Abstract: A s bstract. Studies were designed (a) to determine whether somatostatin is released into the circulation after meals in sufficient amounts to regulate gastric or pancreatic islet function in humans and (b) to investigate the possible role of somatostatin in the pathogenesis of duodenal ulcer disease. Mean plasma somatostatin-like immunoreactivity (SLI) increased from 6.2±1.5 pg/ml to a peak level of 13.8±1.3 pg/ml in eight healthy subjects after a 1,440-cal steak meal (P < 0.005). When somatostatin-14 was inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(44 citation statements)
references
References 23 publications
2
42
0
Order By: Relevance
“…Our results closely agree with other reports showing a similar postprandial SLI increase (4,5,16). Gel-filtration chromatography performed in this laboratory, indicated that roughly 50% of the postprandial SLI corresponded to S-14 in the volunteers under study (15).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our results closely agree with other reports showing a similar postprandial SLI increase (4,5,16). Gel-filtration chromatography performed in this laboratory, indicated that roughly 50% of the postprandial SLI corresponded to S-14 in the volunteers under study (15).…”
Section: Discussionsupporting
confidence: 94%
“…Endocrine action of S-14 via the systemic circulation is supported by several recent studies (4)(5)(6)16). Colturi and coworkers (5) and Holst's group (6) have both independently studied the effects oflow dose infusions of somatostatin on meal-stimulated gastric acid and pancreatic islet cell function.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In addition to its localization in several digestive organs, including the stomach, intestine, biliary tree, and pancreas (4, 5), somatostatin-like immunoreactivity has been demonstrated in the retina (6) in close proximity to both a-and /3-islet cells (7), in the cardiac vagus (8), and in the glomerulus of the kidney (9). It has been suggested that circulating somatostatin may play a physiologic role in the stomach (10,11) and pancreas (12). However, due to its widespread distribution somatostatin is a likely candidate for a local paracrine role in the regulation of various endocrine and exocrine cells (13).…”
Section: Introductionmentioning
confidence: 99%